Solving Large Scale Learning Tasks. Challenges and Algorithms Essays Dedicated to Katharina Morik on the Occasion of Her 60th Birthday - Michaelis, Stefan; Piatkowski, Nico; Stolpe, Marco (Lecture Notes in Artificial Intelligence,, 2016)
In celebration of Prof. Morik's 60th birthday, this Festschrift covers research areas that Prof. Morik worked in and presents various researchers with whom she collaborated. The 23 refereed articles in this Festschrift volume provide challenges and solutions from theoreticians and practitioners on data preprocessing, modeling, learning, and evaluation. Topics include data-mining and machine-learning algorithms, feature selection and feature generation, optimization as well as efficiency of energy and communication.